About a case of a specific complication of monoamniotic twin pregnancy: umbilical cord entanglement - Wade, Mouhamadou; Gueye, Mamour; Mbodji, Aissatou; Ndiaye, Mame Diarra; Sene, Mouhamet; Sow, Pahté; Diallo, Daouda Adama; Sylla, Mouhamed Nazir; Mbaye, Magatte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Monoamniotic twin pregnancies are uncommon and often complicated by umbilical cord entanglement. It is important to investigate a umbilical cord entanglement during antenatal ultrasound examinations. The diagnosis is based on ultrasound with color and pulsed Doppler. Despite the high percentage of cord entanglement, the perinatal mortality rate remains very low. Rigorous ultrasound monitoring and recording of fetal heart rhythms can improve the prognosis. We report a case of umbilical cord entanglement in a monoamniotic twin pregnancy discovered during a caesarean section with a favorable outcome.